Concept maps as a teaching and learning strategy: classification of matter - Blessinger, Patrick (Revista Perspectivas Educacionales (REPED), 2025)
Chemistry forms the basis for all natural sciences. It is referred to as "the central science" as it links physical sciences (like physics and geology) with life sciences (such as biology and medicine). Its study of matter has a crucial role in grasping scientific phenomena. The Classification of Matter concept map (graphic organizer) visually shows how matter is grouped by its physical and chemical traits. Concept maps help students understand and remember the subject better. (Ir a traducción del artículo completo)